Evaluation and comparison of anti-cancer activity of dapagliflozin and canagliflozin in oral cancer cell line: an in vitro study - Vinay, Nenavath; David, Darling Chellathai (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cancer is rapidly evolving life-threatening ailment in the mankind due to changes in daily food intake and lifestyle changes. Oral carcinoma is 6th major cause of cancer death in the world and it is third major reason of cancer mortality in India. Every cell in the human body requires glucose for its metabolic energy. Besides normal cell, cancer cells also require the glucose for its endurance and multiplication. SGLT2 inhibitors which are aimed at diabetes therapy exhibited anticancer properties also in colon and pancreatic cancer lines. Present study aim is to evaluate the anticancer activity of SGLT2 inhibitors against oral cancer cell by MTT Assay. Methods: To evaluate the anticancer activity of SGLT2 inhibitors MTT Cytotoxic assay is performed as per standard protocols. Cancer cells were plated in 24-well plates and incubated at 370C with 5% CO2 condition. After convergence, samples are added to the plates in various concentrations and allowed to incubate then they are detached from the plates and cleansed with the reagents. The wells are coated with the dye and incubated. Later samples are analysed in UV-spectrophotometer. Results: Cytotoxic assay showed decrease in cell viability with increasing dose of SGLT2 inhibitors. IC50 values were determined graphically. The IC50 value of dapagliflozin is 400µg/ml and canagliflozin is 250µg/ml respectively after 24 hours of Assessment. Conclusions: The results of the current study give us an evidence that SGLT2 inhibitors dapagliflozin and canagliflozin exhibits anticancer property in Oral Cancer cell line.